2012
DOI: 10.1289/ehp.1104447
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Residential Infiltration of Outdoor PM2.5in the Multi-Ethnic Study of Atherosclerosis and Air Pollution (MESA Air)

Abstract: Background: Epidemiologic studies of fine particulate matter [aerodynamic diameter ≤ 2.5 μm (PM2.5)] typically use outdoor concentrations as exposure surrogates. Failure to account for variation in residential infiltration efficiencies (Finf) will affect epidemiologic study results.Objective: We aimed to develop models to predict Finf for > 6,000 homes in the Multi-Ethnic Study of Atherosclerosis and Air Pollution (MESA Air), a prospective cohort study of PM2.5 exposure, subclinical cardiovascular disease, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
133
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(143 citation statements)
references
References 36 publications
9
133
1
Order By: Relevance
“…9 Responses, meteorology, and an outdoor PM 2·5 tracer (particulate sulphur assessed in concurrent samples inside and outside selected homes) were used to predict the fraction of ambient PM 2·5 infiltrating homes. 10 Indoor PM 2·5 exposures were calculated as the predicted fortnight's outdoor PM 2·5 concentration multiplied by the weather-specific and residence-specific infiltration fraction. An individually-weighted exposure to ambientderived PM 2·5 (PM 2·5iwa ) for each fortnight was calculated by time-weighting the outdoor concentration by time spent outdoors, and indoor exposure by time spent indoors.…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…9 Responses, meteorology, and an outdoor PM 2·5 tracer (particulate sulphur assessed in concurrent samples inside and outside selected homes) were used to predict the fraction of ambient PM 2·5 infiltrating homes. 10 Indoor PM 2·5 exposures were calculated as the predicted fortnight's outdoor PM 2·5 concentration multiplied by the weather-specific and residence-specific infiltration fraction. An individually-weighted exposure to ambientderived PM 2·5 (PM 2·5iwa ) for each fortnight was calculated by time-weighting the outdoor concentration by time spent outdoors, and indoor exposure by time spent indoors.…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…Indoor aerosols are most commonly a mixture of aerosols that transport from outdoors, and are emitted from indoor sources [41][42][43]. This section explores the impact of the outdoor-to-indoor transport of ambient aerosols alone (i.e., in the absence of indoor sources), while the subsequent section explores the impact of indoor distributions resulting from a combination of both indoor and outdoor sources.…”
Section: How Does the Outdoor-to-indoor Transport Of Ambient Aerosol mentioning
confidence: 99%
“…Mosecomonitoring (a municipal air quality monitoring service of the Moscow Environmental Protection Department) reported that annual average levels of nitrous dioxide in Moscow air have dropped by a factor of 4, while PM 10 , SO 2 and ozone levels have decreased by a factor of 2 since 2002. PM 10 is an important indicator of air pollution and health effects [13,14,15,16,17,18,19,20,21]. However, a downward trend in NO 2 concentrations has lately flattened off because of rapid growth in traffic intensity [12].…”
Section: Epidemiologic Assessment Of Relationship Between Air Pollutimentioning
confidence: 99%